2015
DOI: 10.1016/j.jksus.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of method and time of extraction on total phenolic content in comparison with antioxidant activities in different parts of Achyranthes aspera

Abstract: The main purpose of this study was to evaluate the effect of extraction method with respect to time of exposure on total phenolic content and antioxidant potential of methanolic extracts (95%) from Achyranthes aspera leaves, stem and roots. Total phenolic content (TPC) was determined using the Folin-Ciocalteu method and antioxidant potential was tested using DPPH radical scavenging and FRAP assays. Plant populations aged 60 and 120 days were considered during the study. Overall, highest TPC was evident in matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 24 publications
(20 reference statements)
3
20
0
Order By: Relevance
“…In the present study, plant part and method of extraction were found to be the most important factors in extraction optimization, however time of extraction least affected variation of yield of TPC as well as TFC. Recently, similar observations were made for Clinacanthus nutans [28] and Achyranthes aspera [29] . It can be noted that, TPC and TFC content in the studied plant parts differ significantly from each other and the contents of TPC, and TFC was higher in roots than other plant parts.…”
Section: Resultssupporting
confidence: 76%
“…In the present study, plant part and method of extraction were found to be the most important factors in extraction optimization, however time of extraction least affected variation of yield of TPC as well as TFC. Recently, similar observations were made for Clinacanthus nutans [28] and Achyranthes aspera [29] . It can be noted that, TPC and TFC content in the studied plant parts differ significantly from each other and the contents of TPC, and TFC was higher in roots than other plant parts.…”
Section: Resultssupporting
confidence: 76%
“…3. Conventional methods like CSE and SBAE have been traditionally used for extraction of terpenes, phenolics and other antioxidant compounds 16,17 .…”
Section: Scientific Reports |mentioning
confidence: 99%
“…These enable us in obtaining a better quality and high efficiency of targeted yield from the plant. Hence, one has to optimize the recovery of the metabolites using extraction methods 16,17 .…”
mentioning
confidence: 99%
“…Extraction is the first important step in the recovery and purification of active substrates from biological materials (Tan (Spigno et al, 2007). Moreover, the extraction method and the extraction time are two of the most important factors in the extraction process (Upadhya et al, 2015). Different methods have been used to extract ant alarm pheromones.…”
Section: Efficiency Of Extraction Of Alarm Pheromone Component Relatementioning
confidence: 99%